Perbedaan Indeks Massa Tubuh pada Ibu Hamil dengan Preeklamsi Ringan, Berat, dan Eklamsi di Rumah Sakit Umum Daerah (RSUD) Ciawi - Syamsu Rijal; Fernando Nathaniel; Dean Ascha Wijaya; Joshua Kurniawan (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2023)
Background: Preclampsia is a one of complication in pregnancy characterised by systolic blood pressure ≥140 mmHg and/or diastolic blood pressure ≥90 mmHg and proteinuria (≥300mg/24hours in urine; protein/creatinine ≥0.3; dipstick protein +1; and/or with additional symptoms. Eclampsia is a severe form of preeclampsia where the mother experiences seizures and/or coma. There are various risk factors for preeclampsia and eclampsia, one of which is the mother's body mass index (BMI). Excessive maternal weight before pregnancy, as well as excessive weight gain during pregnancy are at risk for preeclampsia. Methods: This study used medical records from the Ciawi General Hospital in 2020, and cross-sectional observational study was carried out. Pregnant women with eclampsia and preeclampsia were the study's population. This study used total sampling as its sampling method, and body mass index measurements were made using information from medical records. The Kruskall Wallis alternative test was utilized in place of the One Way Anova as the hypothesis test in this investigation. In this investigation, a 5% level of significance is expected. Results: This study involved 190 respondents who met the inclusion criteria. The statistical test results showed no significant difference in mean body mass index between the eclampsia, severe preeclampsia, and mild preeclampsia groups (P-value: 0.688). This difference is expected due to the small number of samples and/or the high variability of the samples. Conclusion: Based on the results of the study, there was no significant association between body mass index and mild, severe, and eclampsia. Further research should be conducted and developed for prevention and lifestyle intervention in preeclampsia.